Crystalglobulin-Associated Kidney Disease: A Case Report and Literature Review - Sophie Leflot; Philippe Leroy; Nathalie Demoulin; Selda Aydin; Guy Touchard; Vincent Javaugue; Marie-Christiane Vekemans; Frank Bridoux; Johann Morelle (Kidney Medicine, 2022)
The kidney is commonly involved in multiple myeloma and other disorders producing monoclonal immunoglobulins. Crystalglobulinemia is a rare condition characterized by spontaneous crystallization and deposition of monoclonal immunoglobulins within the microvasculature of the kidney and other organs, leading to inflammation, ischemia, and end-organ damage. The present case and literature review highlight the clinical spectrum, diagnostic challenges, management, and outcomes of this underrecognized complication of monoclonal gammopathy. Crystalglobulin-associated kidney disease should be suspected in patients with rapidly progressive kidney disease associated with hematuria, proteinuria, extrarenal lesions (ie, skin and joints), and monoclonal gammopathy. Kidney biopsy is critical to the diagnosis, which relies on the identification by ultrastructural analysis of electron-dense crystalline structures composed of a monoclonal immunoglobulin within the kidney microvasculature. Conventional immunofluorescence on frozen tissue frequently fails to detect monoclonal protein deposits, and pronase-based antigen retrieval on paraffin-embedded material or immunoelectron microscopy is required to unmask antigenic epitopes located within crystalline inclusions. Early intervention combining treatment of clonal cell proliferation and plasma exchanges is warranted to reduce the burden of this rare but dramatic complication of monoclonal gammopathy.